Fluoride-free environment-friendly flame-retardant PC material and preparation method thereof
By introducing naphthol cyclic phosphate and methylsiloxane synergistic flame retardant into transparent flame retardant PC materials, the problem that fluorine-free transparent flame retardant PC materials is difficult to achieve UL 94V0 flame retardant at wall thickness of 1.0mm and below, and the high-efficiency flame retardant performance and excellent mechanical properties of fluorine-free environmentally friendly flame retardant PC materials are achieved.
Patent Information
- Application Number
- CN202411978033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
When existing transparent flame retardant PC materials meet the flame retardant requirements of UL 94V0, they usually contain fluorine-free and have a fluorine-free transparent flame retardant effect.
By introducing a naphthol cyclic phosphate flame retardant and a methylsiloxane synergistic flame retardant of a double epoxy head, combined with the flame retardant molecular assembly design principle, a fluorine-free environmentally friendly flame retardant PC material is designed, achieving the UL 94V0 flame retardant performance under fluorine-free conditions.
It has achieved the UL 94V0 flame retardant performance of fluorine-free transparent flame retardant PC material, and it also meets the environmental protection requirements of PFAS, has excellent mechanical properties and flame retardant performance, and is suitable for the automotive industry, electrical instrument industry and machinery industry.
Smart Images

Figure BDA0005220886750000021 
Figure BDA0005220886750000031 
Figure BDA0005220886750000032
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer materials, and in particular to a fluorine-free, environmentally friendly, flame-retardant PC material, a material preparation method and application. Background Art
[0002] Polycarbonate (PC) is an amorphous polymer that becomes a transparent glass after melting and cooling. It has excellent optical and mechanical properties, excellent high and low temperature resistance, low water absorption, good impact resistance, insulation and aging resistance, and can withstand corrosion from inorganic and organic dilute acids, and has a certain degree of chemical corrosion resistance. Transparent flame-retardant PC has the above-mentioned performance advantages of PC materials and excellent flame retardant properties, meeting the performance requirements of PC in application scenarios such as electronic appliances, instruments and meters, communication media and data optical disks. However, it is extremely technically difficult to meet the UL 94V0 flame retardancy while achieving a transmittance of more than 85%.
[0003] The full name of PFAS in English is per / polyfluoroalkyl substances, i.e. perfluoroalkyl and polyfluoroalkyl compounds. PFAS has extremely high chemical stability and bioaccumulation, is difficult to degrade, can persist in the environment, and poses a serious threat to the environment and human health. The EU has proposed a proposal to comprehensively restrict the production and use of PFAS in Europe, involving more than 10,000 substances. The UK is also investigating the hazards of PFAS and considering restrictive measures on the basis of REACH regulations. The United States has imposed additional reporting requirements on 329 PFAS substances to ensure risk assessment before use. PFAS contains polytetrafluoroethylene (PTFE), a flame retardant and anti-drip agent commonly used in flame retardant PC. The development of a fluorine-free flame retardant PC has become a hot topic in the industry.
[0004] Chinese invention patent CN113801453A discloses a halogen-free flame-retardant transparent PC material and its products, wherein the flame retardant is a compound of one or more of phenoxy cyclophosphazene and vinylphenylsilane; and it cooperates with an anti-dripping agent. The use of the halogen-free flame-retardant transparent PC material and its products of the present invention solves the problem that the PC material cannot reach the flame retardant grade of 0.2mmVTM-0 and the transmittance drops below 70%, and also makes the PC material have good flame retardancy and retains the good physical properties of the PC material itself. Chinese invention patent CN103602052A discloses a transparent flame-retardant PC material, wherein the synergistic flame retardant contains three flame retardant elements of P, N and Si at the same time, and has an excellent synergistic flame retardant effect with the sulfonate flame retardant. Adding a very small amount of flame retardant can make the flame retardant performance of the 1.2mm thick strip reach UL94V-0 level. Chinese invention patent CN109627728A provides a PC / PETG alloy material with good weather resistance, halogen-free flame retardancy and low temperature performance. By adding phosphorus-silicon mixed flame retardant, the flame retardant synergistic effect is significant, and the mechanical properties can maintain the best balance; without adding ultraviolet additives, the material has excellent weather resistance and can meet outdoor use; without affecting the transmittance of halogen-free flame retardant PC / PETG alloy material, it is toughened to ensure that the material has good impact performance. Transparent flame retardant PC materials have been studied and applied a lot, but the current research has the following problems: transparent flame retardant PC that meets UL 94VO for products with a wall thickness of 1.0 mm and below usually contains fluorine elements, and the disclosed inventions of maintaining fluorine-free transparent flame retardant PC usually only meet the requirements of a wall thickness of 1.0 mm. The disclosed inventions are mainly aimed at the development of flame retardant and anti-dripping agents to replace PTFE. The development of transparent flame retardant PC based on the principle of flame retardant molecular assembly design has important research significance for achieving UL94 V0 for products with a wall thickness of 1.0 mm and below. Summary of the invention
[0005] In order to fill the gap in the prior art, the present invention provides a fluorine-free environmentally friendly flame-retardant PC material, a material preparation method and application. According to the flame retardant molecular assembly design principle, a new flame retardant and a synergistic flame retardant are introduced into the formula design to achieve flame-retardant PC meeting the UL94 V0 flame retardant requirement. At the same time, the flame-retardant PC material composition meets the PFAS environmental protection requirements. The flame-retardant PC prepared by the method can be applied to the automotive industry, electrical instrument industry, machinery industry and other fields.
[0006] The present invention is achieved through the following technical solutions:
[0007] A fluorine-free, environmentally friendly, flame-retardant PC material, a material preparation method and an application, characterized in that: the raw material composition is as follows in parts by weight:
[0008]
[0009] The polycarbonate resin has a number average molecular weight of 17000-40000, a weight average relative molecular mass of 20000-50000, a melt flow rate (test condition: 300° C.*1.2 kg): 10-25 g / 10 min, and a light transmittance (test standard: GB / T 2410-2008) ≥85%.
[0010] The flame retardant is a naphthol cyclic phosphate with a density of 1.24±0.2g / cm3 and a structural formula as follows:
[0011]
[0012] The synergistic flame retardant is a diepoxy-capped methylsiloxane with a density of 1.113±0.06 g / cm3 and a silicon content of 12-14%. The structural formula is as follows:
[0013]
[0014] The other auxiliary agents may be one or more of antioxidants, lubricants, toughening agents, heat-resistant agents, and colorants.
[0015] The method for preparing the transparent, environmentally friendly, flame-retardant PC material comprises the following steps:
[0016] (1) Weigh various raw materials according to the formula ratio; mix the polycarbonate resin, flame retardant, synergistic flame retardant, antioxidant, processing aid, toughening agent, heat resistant agent, etc. evenly with a high-speed mixer and set aside.
[0017] (2) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and after melt extrusion, granulation, drying and other processes at 220-240° C., the fluorine-free, environmentally friendly, flame-retardant PC material is obtained.
[0018] The above-mentioned fluorine-free flame-retardant PC material can be applied to the fields of automobile industry, electrical instrument industry and mechanical industry.
[0019] The advantage of the present invention is that according to the principle of flame retardant molecular assembly design, a naphthol ring phosphate flame retardant is introduced in the formula design, carbon monoxide is produced during the combustion of PC to play a gas phase flame retardant effect, and thermal decomposition occurs at high temperature. The water and acidic substances produced by the decomposition of the flame retardant can dilute the combustibles. At the same time, the released gas can isolate oxygen or dilute the combustible gas. The phosphorus element has a high reactivity and can react chemically with the hydrogen element in the combustible to generate non-flammable phosphorus-containing compounds, thereby reducing the combustibility of the combustibles. The structure of the naphthol ring has excellent carbonization at high temperature, can form a protective carbon layer, has the function of heat insulation and oxygen isolation to prevent dripping and ignition, and the flame retardant contains the synergistic effect of silicon and phosphate structure, which further improves the flame retardant efficiency. Synergistic flame retardant siloxane can play a synergistic role with the flame retardant to improve the high temperature thermal stability and graphitization degree of the condensed phase carbon layer, the active epoxy group can improve the melt strength of PC, solve the problem of dripping and ignition during PC combustion, and the synergistic effect of the flame retardant, the synergistic flame retardant and the tackifier further improve the flame retardant performance. The flame-retardant PC material prepared by the present invention exhibits excellent mechanical properties and flame-retardant properties.
[0020] The beneficial effects of the present invention are:
[0021] 1) The present invention selects a naphthol ring phosphate flame retardant according to the combustion characteristics of PC materials. Carbon monoxide is produced during the combustion of PC to play a gas phase flame retardant effect. At the same time, the flame retardant has a phosphate structure, and the water and acidic substances produced by its decomposition can dilute the combustibles. At the same time, the released gas can isolate oxygen or dilute the combustible gas. The phosphorus element has a high reactivity and can react chemically with the hydrogen element in the combustibles to generate non-flammable phosphorus-containing compounds, thereby reducing the combustibility of the combustibles. The naphthol ring structure has excellent carbonization properties and can form a protective carbon layer, which has the function of heat insulation and oxygen isolation to prevent dripping and ignition.
[0022] 2) The present invention selects methyl siloxane with a diepoxy cap as a synergistic flame retardant. The silicon element in the synergistic flame retardant can play a carbonizing role, thereby improving the high-temperature thermal stability and graphitization degree of the condensed phase carbon layer. Increasing the thickness of the carbon layer can effectively improve the flame retardant efficiency, and has good compatibility with PC and does not affect its flame retardant effect.
[0023] 3) The present invention selects epoxy groups in the synergistic flame retardant to react with the terminal groups of the PC resin to increase its melt strength and play an anti-dripping effect during the combustion process.
[0024] 4) The naphthalene ring structure and synergistic flame retardant in the flame retardant of the present invention further enhance the high-temperature thermal stability and graphitization degree of the condensed phase carbon layer, and play an anti-dripping effect during the combustion process, thereby enhancing the flame retardant properties of the PC material.
[0025] 5) The flame-retardant PC prepared by the present invention does not contain fluorine element, meets the environmental protection requirements of PFAS, and has excellent mechanical properties and flame retardant properties.
[0026] Through the above beneficial effects, the flame-retardant PC material has excellent mechanical properties and flame retardancy, and is endowed with environmental protection concepts and high performance characteristics. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] The embodiments and comparative examples of the present invention use the following materials, but are not limited to the following materials:
[0029] PC, product name 2805, produced by Covestro;
[0030] Flame retardant, commercially available;
[0031] Synergistic flame retardant, commercially available;
[0032] Styrene-acrylonitrile copolymer T-SAN, commercially available;
[0033] Bisphenol A-bis(diphenyl phosphate) BDP, trade name WSFR-BDP, produced in Wansheng, Zhejiang;
[0034] Sulfonate flame retardant, trade name PCFR-HS, produced by 3M
[0035] Dripping agent PTFE, trade name DB105, produced by Suzhou Profe;
[0036] Organic siloxane flame retardant, trade name ADDITIVE 40-001, produced by Dow Corning;
[0037] Toughening agent MBS, trade name M732, produced in Japan;
[0038] Lubricant, PETS, commercially available;
[0039] Antioxidant 1010, commercially available;
[0040] Antioxidant 168, commercially available;
[0041] Preparation methods of Examples 1-5 and Comparative Examples 1-7:
[0042] Preparation method of flame retardant PC material
[0043] (1) Weigh various raw materials according to the formula ratio; mix the polycarbonate resin, flame retardant, synergistic flame retardant, antioxidant, processing aid, toughening agent, heat resistant agent, etc. evenly with a high-speed mixer and set aside.
[0044] (2) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and after melt extrusion, granulation, drying and other processes at 220-240° C., the fluorine-free, environmentally friendly, flame-retardant PC material is obtained.
[0045] Preparation of flame retardant PC material test specimens:
[0046] The above materials were dried in a forced air drying oven at 120° C. for 4 hours and then injection molded into standard specimens at an injection molding temperature of 220-270° C. The prepared mechanical properties specimens were conditioned in a standard laboratory environment (23° C., 50% RH) for 24 hours before testing.
[0047] Test methods for each performance index:
[0048] Tensile properties: According to ISO 527 method, sample size: 170*10*4mm, test speed 5mm / min.
[0049] Bending properties: According to ISO 178 method, sample size: 80*10*4mm, test speed 2mm / min.
[0050] Notched impact performance: According to ISO 179 method, sample size: 80*10*4mm.
[0051] Flame retardant performance: According to UL94 method, sample size: 127*12.7*1.6mm.
[0052] Table 1: Composition and properties of flame retardant PC materials in Examples 1-5 and Comparative Examples 1-3
[0053]
[0054]
[0055] It can be seen from the results of the embodiments and comparative examples in Table 1 that the present invention can achieve UL 94V0 flame retardancy without adding fluorine-containing flame retardants. According to Examples 1-4 and Comparative Examples 1-3, the naphthol cyclic phosphate used in the present invention has a more excellent flame retardant efficiency than the flame retardant BDP. Under the condition of the same amount of synergistic flame retardant added, the amount of flame retardant added to achieve the same flame retardant grade is less. This is because the flame retardant used in the present invention has the effects of gas phase flame retardancy and condensed phase flame retardancy, and the naphthol ring structure has excellent carbonization, which can form a protective carbon layer, and has the function of heat insulation and oxygen isolation to prevent dripping and ignition. It can be seen from Examples 1-2, Example 5 and Comparative Example 1 that the synergistic flame retardant of the present invention can achieve the effect of the anti-dripping agent PTFE under the premise of increasing the addition amount. It can be seen from Examples 1, Examples 3-5 and Comparative Examples 2-3 that the effect of the synergistic flame retardant of the present invention is better than that of the conventional silicon-based flame retardant. This is because the synergistic flame retardant contains reactive epoxy groups in addition to silicon elements, which can react with the terminal groups of the PC resin to increase its melt strength and play an anti-dripping effect during the combustion process. The flame retardant of the present invention does not contain toxic gases or smoke during the combustion process of the flame retardant, and is harmless to the environment and the human body. The flame retardant PC material composition meets the PFAS environmental protection requirements and belongs to an environmentally friendly material. The prepared fluorine-free environmentally friendly flame retardant PC material is used in the automotive industry, electrical instrument industry, machinery industry and other fields.
Claims
1. A fluorine-free, environmentally friendly, flame-retardant PC material, characterized by: According to the following raw material composition by weight percentage: The flame retardant is a naphthol cyclic phosphate with a density of 1.24±0.2g / cm 3 , the structural formula is as follows:
2. The fluorine-free, environmentally friendly, flame-retardant PC material according to claim 1, characterized in that: The polycarbonate resin has a number average molecular weight of 17000-40000, a weight average relative molecular mass of 20000-50000, a melt flow rate of 10-25 g / 10 min, and a light transmittance of ≥85%.
3. The fluorine-free, environmentally friendly, flame-retardant PC material according to claim 1, characterized in that: The synergistic flame retardant is a diepoxy-capped methylsiloxane with a density of 1.113±0.06 g / cm 3 , silicon content 12-14%, the structural formula is as follows:
4. The fluorine-free, environmentally friendly, flame-retardant PC material according to claim 1, characterized in that: The other auxiliary agents may be one or more of antioxidants, lubricants, toughening agents, heat-resistant agents, and colorants.
5. The method for preparing the fluorine-free, environmentally friendly, flame-retardant PC material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Weigh various raw materials according to the formula ratio; mix the polycarbonate resin, flame retardant, synergistic flame retardant, antioxidant, processing aid, toughening agent, heat resistant agent, etc. evenly with a high-speed mixer and set aside; (2) The resin and additive mixture is added through the main feed port of a twin-screw extruder, and after melt extrusion, granulation, drying and other processes at 220-240° C., the fluorine-free, environmentally friendly, flame-retardant PC material is obtained.
Citation Information
Patent Citations
Transparent flame-retardant PC material, and preparation method thereof
CN103602052A
Transparent weather-proof halogen-free flame retardant PC / PETG alloy material
CN109627728A
Halogen-free flame-retardant transparent PC material and product
CN113801453A
Inert closed-pore perlite fire-insulation heat-insulation wallboard
CN108341622A
Fluorine-free halogen-free flame-retardant PC plastic and preparation method thereof
CN117327382A
Cited By
Flame-retardant PC (polycarbonate) material as well as preparation method and application thereof
CN120271994A
Polycarbonate material composition, polycarbonate material as well as preparation method and application of polycarbonate material
CN121610049A
Fluoride-free flame-retardant transparent polycarbonate material as well as preparation method and application thereof
CN121699363A
Fluorine-free flame-retardant transparent polycarbonate material and preparation method and application thereof
CN121699363B